Proceedings of the Ocean Drilling Program, 156 Scientific Results 1997
DOI: 10.2973/odp.proc.sr.156.001.1997
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineralogy and clay geochemistry in the vicinity of the décollement zone, northern Barbados Ridge

Abstract: Fine-grained sediments recovered during Leg 156 of the Ocean Drilling Program contain assemblages of clay minerals that change considerably with depth. Key structural and stratigraphic features within the toe of the northern Barbados accretionary prism include the basal décollement and a sharp boundary between lithologic Units II and III; this lithologic boundary occurs within the décollement zone. We analyzed three size fractions (4−8 µm, 1−4 µm, and <1 µm) by X-ray diffraction and obtained chemical data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…In contrast, V p (measured at atmospheric pressure) in sediments from ODP Site 808 (outer marginal trench wedge to USB and LSB, between 400 and 950 mbsf) is lower in the vertical (i.e., core parallel) direction than in the horizontal direction (irrespectively of azimuth) by up to ∼10% [ Brückmann et al , 1993]. In accreted sediments within the Barbados accretionary complex, Brückmann et al [1997] reported either positive anisotropy (i.e., horizontal V p faster than vertical one), mostly between 0% and +4%, in hole 948C or no anisotropy in hole 949B (both claystone with total clay content mostly around or above 60%) [ Underwood and Deng , 1997), without a clear explanation for the difference between the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, V p (measured at atmospheric pressure) in sediments from ODP Site 808 (outer marginal trench wedge to USB and LSB, between 400 and 950 mbsf) is lower in the vertical (i.e., core parallel) direction than in the horizontal direction (irrespectively of azimuth) by up to ∼10% [ Brückmann et al , 1993]. In accreted sediments within the Barbados accretionary complex, Brückmann et al [1997] reported either positive anisotropy (i.e., horizontal V p faster than vertical one), mostly between 0% and +4%, in hole 948C or no anisotropy in hole 949B (both claystone with total clay content mostly around or above 60%) [ Underwood and Deng , 1997), without a clear explanation for the difference between the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Sedimentary clay mineral composition is more difficult to determine, as the clays are both finer‐grained and more reactive than the other clasts. However, clay‐mineral analysis of other accretionary wedge and trench sediments suggests that these rocks probably contained a variety of sedimentary clay minerals such as chlorite, illite, smectite, kaolinite and montmorilinite, and some mixed‐layer clays [i.e., Karnosov et al , 1977; Karpoff , 1992; Underwood and Deng , 1997] (ODP‐Leg 185). Clay minerals have variable, but high, water contents; ideal kaolinite (Al 2 Si 2 O 5 (OH) 4 ) contains 14 wt.% H 2 O and most illites contain ∼10 wt.% H 2 O (for comparison, white‐micas, stabilized at higher grades by the breakdown of clays, contain ∼5 wt.% H 2 O).…”
Section: Discussionmentioning
confidence: 99%
“…Sedimentary clay mineral composition is more difficult to determine, as the clays are both finer-grained and more reactive than the other clasts. However, clay-mineral analysis of other accretionary wedge and trench sediments suggests that these rocks probably contained a variety of sedimentary clay minerals such as chlorite, illite, smectite, kaolinite and montmorilinite, and some mixed-layer clays [i.e., Karnosov et al, 1977;Karpoff, 1992;Underwood and Deng, 1997] [25] As these sediments progressed downward in the subduction zone, they underwent mineralogical changes that must have resulted in significant chemical redistribution, at least at the local scale. Even the lowest-grade rocks of the Coastal Belt differ from likely sedimentary protoliths in several important ways.…”
Section: Evidence For Devolatilization and Effects On Rock Compositionmentioning
confidence: 99%
“…Because the composition of our illite/ quartz gouge is similar to that of the protolith sediment at many subduction margins (e.g. Steurer and Underwood 2003;Underwood and Deng 1997), the temperaturedependent frictional behaviour described here is directly relevant to understanding temperature-and depth-dependent transitions in slip stability along subduction megathrusts.…”
Section: Implications For Subduction Megathrust Seismogenesismentioning
confidence: 99%